Direct photolysis of MeO-PBDEs in water and methanol: Focusing on cyclization product MeO-PBDFs. (November 2015) - Xue, Weifeng; Chen, Jingwen; Xie, Qing; Zhao, Hongxia
Graphical abstract: Highlights: MeO-PBDEs have faster direct photolysis and higher quantum yields in methanol than in water. Photocyclization to form MeO-PBDFs can only occur in the methanol solution of 5-MeO-BDE-47. Density functional theory predicted the photocyclization pathways and unveiled the mechanisms. Intra-annular H-elimination assisted by a Br cleaved from an ortho -C–Br bond favors the photocyclization. Photocyclization of MeO-PBDEs depends on not only the Br-substitution patterns but also the solvent environments. Abstract: Polybrominated diphenyl ethers (PBDEs) and hydroxylated PBDEs can transform into polybrominated dibenzofurans (PBDFs) via photocyclization. However, it is unclear whether methoxylated PBDEs (MeO-PBDEs) can photocyclize to form MeO-PBDFs. In this study, 5-MeO-BDE-47, 5′-MeO-BDE-99 and 6-MeO-BDE-85 were selected as models to investigate their direct photolysis, especially photocyclization in two solvent environments (water and methanol) using simulated photochemical experiments and density functional theory (DFT) calculations. The experimental results showed that MeO-PBDEs had faster direct photolysis reactions and higher quantum yields in methanol, and MeO-PBDFs could only be formed in a methanol solution of 5-MeO-BDE-47. The DFT results indicated that the lowest excited triplet state MeO-PBDEs can form dibenzofurans via direct cyclization pathways. Intra-annular H-elimination was found to be the rate-determining step for most cyclization pathways with high reaction barriers (⩾19.7 kcal/mol), while 5-MeO-BDE-47 was found to have a distinct pathway for which the rate-determining step is ring closure with a low barrier (13.8 kcal/mol) in a methanol environment. For this pathway, H-elimination assisted by Br cleaved from an ortho -C–Br bond was observed with a 2.0 kcal/mol barrier. Thus, the DFT results reasonably explained the experimental findings, and the photocyclization of MeO-PBDEs depended on the specific Br-substitution patterns and specific effects of the environmental media.